L.F. OBUKHOVA: 2002–2016 - Janna M. Glozman (Национальный психологический журнал, 2019)
Background. Psychology Department of Moscow Lomonosov State University together with Russian Psychological Association has celebrated the 80th birth anniversary of Lyudmila Obukhova. She was an outstanding world known expert in developmental psychology, mental development, family and child matters, etc. The Objective is to analyze t fruitful scientific and personal achievements of Lyudmila Obukhova of the 15 last years of her life that are uncovered by her colleagues at the Psychology Department of Moscow Lomonosov State University. Design. The paper describes our collaboration with Lyudmila Obukhova in 2002-2016: lecturing trips, participation in international congresses and conferences, e.g. the 2nd Congress of the International Association of Cultural Research (ISCAR) in San Diego, USA; the first International Vygotsky memorial Conference in Lisbon, Portugal; the XX International Congress of gerontology in Seoul, South, Korea; the first International Congress on child psychology in Braga, Portugal; The 6th International Conference on Nutrition and Physical Activity in Taipei, Taiwan’; The 7th International Conference on Cognitive Sciences in Svetlogorsk, ethnographic expedition in Kamchatka and more. An integration of various research issues and their international value should be underlined as well as Obukhova’s exceptional personality and communication talent. Conclusion. Obukhova’s array of interests is identified, her personality is revealed, her unusual gift of communication is shown. International recognition of her research is revealed.